Effects of Braprost sodium in the treatment of arteriovenous fistula in diabetes mellitus patients - LU Zhi-feng (Linchuang shenzangbing zazhi)
Objective To study the effects of beraprost sodium in the treatment of arteriovenous fistula in diabetes mellitus patients.Methods Forty diabetes mellitus patients subjected to venous fistula surgery were enrolled in this study and were randomly assigned into beraprost sodium therapy group(treatment group,n = 20) or control group in = 20).Volume of blood flow and maturing rate of fistula 6 weeks after operation,and thrombosis rate within one year were measured.Routine blood analyses,changes of blood coagulation,and adverse drug reactions were compared between the two groups.Results Before treatment,the two groups had no significant difference in age,gender,vessel diameter,liver function,renal function,routine blood and blood coagulation analyses.At 6th week after operation,volume of blood flow and maturing rate of fistula,and thrombosis rate within one year in treatment group and control group were(395.4 + 98.6) ml/min,95%and 5%,and(304.5 ± 86.4)ml/min,80%and 255,respectively.There was significant difference between the two groups(P<0.05).But routine blood analyses and blood coagulation changes showed no significant differences between the two groups(P>0.05).Conclusions Beraprost sodium can increase volume of blood flow and maturing rate of fistula 6 weeks after operation,and reduce thrombosis rate within one year postoperation.